Challenges in Recruiting U.S. Farmers for Policy‐Relevant Economic Field Experiments. Issue 2 (28th September 2020) - Weigel, Collin; Paul, Laura A.; Ferraro, Paul J.; Messer, Kent D.
Abstract: To develop evidence‐based agricultural policies, researchers increasingly use insights from economic field experiments. These insights are often limited by the challenges of recruiting large and representative samples of farmers. To improve the effectiveness and cost efficiency of farmer recruitment, researchers should apply the same experimental methods to the recruitment process that they apply to their main research questions. Here we experimentally evaluate ten recruiting strategies in two large‐scale, high stakes experiments. We find that monetary incentives and reminders are effective, but costly. Costless strategies, such as prominently citing a well‐known institution as the sponsor, had positive but small, effects on recruitment.